Concentración de lactato versus diseño y dificultad de la pista en BMX - Mateo-March, M.; Zabala, M.; Blasco-Lafarga, C.; Guzman, J. F. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
This paper analyzes whether lactate production presents a specific dynamic according to the phases of a BMX race, and its possible relationship to the difficulty / design of the track. Nine Spanish national team athletes performed three types of bouts: No pedaling (NP), Pedaling only the Exit Ramp (PRS) and Pedaling Freely (PL) in three days and tracks of varying difficulty: High (AD), Medium (MD) and Low (BD)-randomized order, counterbalanced and with recoveries of 10 min. Our results attribute the 11.7% of lactate production to the initial acceleration (PRS; greater at higher difficulty), 65.7% to drive actions (NP), and 22.6% to the ending pedaling. The repeated measures ANOVA shows differences (p <0.000) in favor of PL, differences that remain when considering difficulty pedaling (p <0.022). The factor "difficulty", affected by the design of the track, affects the lactate production as difficulty influences the feasible "technique" in each phase.